2014
DOI: 10.1039/c4nr00412d
|View full text |Cite
|
Sign up to set email alerts
|

A one-step green route to synthesize copper nanocrystals and their applications in catalysis and surface enhanced Raman scattering

Abstract: A nontoxic, simple, inexpensive, and reproducible strategy, which meets the standard of green chemistry, is introduced for the synthesis of copper nanocrystals (Cu NCs) with olive oil as both reducing agent and capping agent. By changing the reaction parameters, the shape, size and surface structure of the Cu NCs can be well controlled. The obtained Cu nanocubes show excellent catalytic properties for the catalytic reduction of dyes and CO oxidation. Moreover, the prepared Cu nanocubes as substrates exhibit su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…Among them, Cu is one of the most promising substrate materials considering its advantages of being low cost, and having strong adsorbability with organic molecules as well as a simple and environmentally friendly preparation process. 2,3 However, compared with Ag and Au, which are the focused noble metal SERS substrates of a number of papers, Cu NPs have attracted less attention because of their high activity in air and insignificant SERS enhancement. 4,5 Recently, some research studies showed that, with a delicate 3D nanoscale structure [6][7][8] or the controlled synthesis of highly ordered assemblies, 9 Cu-based substrates can exhibit an excellent SERS enhancement effect almost on the same level as Au and Ag.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Cu is one of the most promising substrate materials considering its advantages of being low cost, and having strong adsorbability with organic molecules as well as a simple and environmentally friendly preparation process. 2,3 However, compared with Ag and Au, which are the focused noble metal SERS substrates of a number of papers, Cu NPs have attracted less attention because of their high activity in air and insignificant SERS enhancement. 4,5 Recently, some research studies showed that, with a delicate 3D nanoscale structure [6][7][8] or the controlled synthesis of highly ordered assemblies, 9 Cu-based substrates can exhibit an excellent SERS enhancement effect almost on the same level as Au and Ag.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Among these materials, nano copper has always been a hot issue specifically due to its low processing costs and potential applications in lubrication, electrical and thermal conductivity, nanofluids, and catalytic reactions, [8][9][10][11][12] while the basic properties of Cu colloidal particles mainly depend on their size, shape, crystallinity and structure, which exactly determine their practical applications. [1][2][3][4][5][6][7] Among these materials, nano copper has always been a hot issue specifically due to its low processing costs and potential applications in lubrication, electrical and thermal conductivity, nanofluids, and catalytic reactions, [8][9][10][11][12] while the basic properties of Cu colloidal particles mainly depend on their size, shape, crystallinity and structure, which exactly determine their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] In the past few decades, in particular, a large number of Pd, [12][13][14] Ru, 15 Rh, 16,17 Pt, 18,19 Au, 20 and Ru-Pt bimetallic 21 catalysts have shown superior activities in both homogeneous and heterogeneous reactions. Iridium (Ir), like other noble metals, shows a wide variety of potential applications in the field of catalysis for many chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Metal nanostructures have attracted considerable interest owing to their preferable properties and potential applications in electronics, 1 sensing, 2,3 medicine, 4,5 imaging, 6,7 and especially in the field of catalysis. [8][9][10][11] In the past few decades, in particular, a large number of Pd, [12][13][14] Ru, 15 Rh, 16,17 Pt, 18,19 Au, 20 and Ru-Pt bimetallic 21 catalysts have shown superior activities in both homogeneous and heterogeneous reactions. Iridium (Ir), like other noble metals, shows a wide variety of potential applications in the field of catalysis for many chemical reactions.…”
Section: Introductionmentioning
confidence: 99%